Pengaruh Disiplin Kerja, Komunikasi dan Kepemimpinan Terhadap Turnover Intention dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PDAM Kota Padang - Regi Mardika; Mondra Neldi; Chintya Ones Charli (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of work discipline, communication, and leadership on turnover intention, with job satisfaction serving as an intervening variable, at PDAM Kota Padang. The study employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 software for analysis. The study population and sample consist of employees from PDAM Kota Padang. The results indicate a significant influence of work discipline on job satisfaction and a significant influence of communication on job satisfaction; however, the influence of leadership on job satisfaction is not significant. Regarding turnover intention, there is a significant influence from work discipline, whereas the influences of communication and leadership are not significant. Job satisfaction has a significant influence on turnover intention. Furthermore, job satisfaction mediates the relationship between work discipline and turnover intention, as well as the relationship between communication and turnover intention; however, it does not mediate the relationship between leadership and turnover intention.